Organizational climate and job satisfaction in the investment company fyd SAC - Hospinal Escajadillo, Sandro (2013)
The article discusses a research project to determine i) the current level of organizational climate and job satisfaction, ii) the relationship between the two variables and ii) the main critical factors affecting each in the company F y D Investments S.A.C.